Work Environment and Teachers’ Job Performance in Public Primary Schools in Ondo State Nigeria - Femi Idowu Aladetan (International Journal of Education, Teaching, and Social Sciences, 2023)
The apparent indiscipline and low quality education in primary schools calls for a serious concern. It is observed that teachers are not performing their duties as expected and this could be as a result of perceived poor work environment hindering effective performance of teachers’ duties. Therefore, this study examined work environment and teachers’ job performance in public primary schools in Ondo State, Nigeria. The descriptive research design of the survey type was employed. The sample consisted of 120 teachers and 20 head teachers randomly selected from 20 public primary schools in Akoko South West Local Government Area of Ondo State. Two researcher-made questionnaires entitled “Work Environment Questionnaire (WEQ)” and “Teachers’ Job Performance Questionnaire (TJPQ)” were used to elicit response from the respondents. The test re-test method was used to test the reliability of WEQ and TJPQ which yielded coefficients of 0.89 and 0.77 respectively. Four research questions were raised and answered using frequency counts, percentage, and mean, while three hypotheses were formulated and tested at 0.05 level of significance using Pearson Product Moment Correlation. The findings revealed that school location was moderately conducive for teachers’ work; the level of interpersonal relationship among teachers was high and the provision of physical facilities was moderate. The findings also revealed that there was significant relationship between school location and teachers’ job performance (r = 0.310, p = 0.001); and there was significant relationship between provision of physical facilities and teachers’ job performance (r = 0.578, p = 0.000). The study therefore concluded that work environment enhanced job performance of the teachers. Based on the findings and conclusion, it was recommended that physical facilities such as conducive office space, potable water and constant electricity should be provided to aid teachers’ job performance